Advanced Glycation End Product Blocker Drugs Have a Great Potential to Prevent Diabetic Cardiomyopathy in an Animal Model of Diabetes Mellitus Type-2. (27th March 2022) - Heydari, Amir Hossein; Fathi, Mojtaba; Heydari, Sophia; Heidari, Mohammad Esmaeil
Abstract : Introduction. Sphingosine 1 phosphate (S1P) is a product of the sphingosine kinase 1 (SphK1) enzyme. Increased S1P can lead to tissue fibrosis that is also one of the pathways for developing diabetic cardiomyopathy. Advanced glycation end products (AGEs) increase S1P in cells. The study is aimed at using aminoguanidine (AG) as an AGEs blocker drug to prevent diabetic cardiomyopathy. Materials and methods. 210 rats were enrolled in the study. Diabetes mellitus type-2 was induced, and rats were divided into AG treated diabetic and nondiabetic groups. The heart histology was assessed with Masson's trichrome and hematoxylin-eosin staining. Cardiac function was measured with transthoracic echocardiography. S1P level and SphK1 gene expression were measured by western-blot and RT-qPCR, respectively. Results. Results showed that S1P level increases in diabetes, and its augmentation in cardiac tissue with K6PC-5 leads to cardiac fibrosis. 50 and 200 mg/kg of AG prevented cardiac fibrosis, but 100 mg/kg had no significant preventive effect. AG suppressed the SphK1 gene expression and reduced the fibrotic effect of S1P. AG preserved cardiac function by keeping ejection fraction and fractional shortening within the normal range in diabetic rats. Conclusion. AG has a suppressor effect on SphK1 gene expression besides its AGEs blocker role. AG is a potential drug to use in diabetic patients for preventing the development of diabetic cardiomyopathy. Other drugs that have AGEs or S1P blocker effects are a good choice for diabetic cardiomyopathy prevention.